Effect of Epidermal Growth Factor in a Patient with Diabetic Hand - Derya KAYA; Gökhan VATANSEVER; Murat Celal SÖZBİLEN; Meltem IŞIKGÖZ TAŞBAKAN (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Diabetes mellitus, a multisystemic disease, is associated with microvascular and macrovascular complications in most patients due to the its chronic course. Although diabetic hand infections are rarer than diabetic foot infections, its development is intricate. Herein, we report the case of a 38-year-old man with type 1 diabetes and restless leg syndrome who presented to our out-patient clinic with a necrotic wound on his right thumb. Despite attempts of needle aspiration, surgical procedures, and oral antibiotics, the wound worsened and underwent necrosis. Therefore, surgical debridement was performed by an orthopedist. Upon achieving healing and granulation tissue formation, epidermal growth factor was topically applied twice a day. The patient was discharged with a prescription for doxycycline and topical epidermal growth factor. Follow-up at 1 and 2 months after discharge revealed ongoing wound healing. In conclusion, the treatment and follow-up of diabetic hand infections should involve a comprehensive multidisciplinary approach. Furthermore, conservative treatments such as appropriate antibiotherapy, wound care and blood sugar regulation should be prioritized over amputation. Moreover, epidermal growth factor is a valuable therapeutic option, with its topical application being an advantage.